Evaluation of dental fear in children with and without dental trauma experience by using CFSS-DS questionnaire - Ivančić Jokić, Nataša (2008)
The paper shows the results of evaluation of dental fear in childeren with and without dental trauma expirience. CFSS-DS questionnaire is used.